NUMERICAL EXPERIMENTS OF WORK OF KINEMATIC WALLS OF ASEISMIC BUILDINGS - A. K. Jusupov; M. A. Abakarov (Вестник Дагестанского государственного технического университета: Технические науки)
Seismically active areas of Earth are built up more and more every year, and earthquakes bring big material and moralny damages. As a result of long searches and researches we developed kinematic walls which possess good adaptive (adapting) properties, and they, are quite acceptable for practical application. As show the numerous researches conducted by us on physical models and with use of the computer, efficiency of kinematic designs offered here is rather high: here seismic forces it is less в 5, 10, 15 times, than in buildings on the usual bases.